Transdermal Drug Delivery Systems: A Focused Review of the Physical Methods of Permeation Enhancement - Rifath Sheikh Vaseem; Alison D'cruz; Srishti Shetty; Hafsa -; Aditya Vardhan; Shreya Shenoy R; Shirleen Miriam Marques; Lalit Kumar; Ruchi Verma (Tabriz University of Medical Sciences, 2024)
The skin is the body's largest organ and serves as a site of administration for various medications. Transdermal drug delivery systems have several advantages over traditional delivery systems. It has both local and systemic therapeutic properties. Controlled plasma drug levels, reduced dosing frequency, and avoidance of hepatic first-pass metabolism are just a few of these systems' advantages. To achieve maximum efficacy, it is critical to understand the kinetics, physiochemical properties of the drug moiety, and drug transport route. This manuscript focused on the principles of various physical means to facilitate transdermal drug delivery. Some examples are iontophoresis, electrophoresis, photomechanical waves, ultrasound, needleless injections, and microneedles. Mechanical, chemical, magnetic, and electrical energy are all used in physical methods. A major advantage of physical methods is their capability to abbreviate pain, which can be used for effective disease management. Further investigation should be carried out at the clinical level to understand these methods for effective drug delivery.